ChemInform Abstract: A Novel Stable Hydrogen‐Rich SnH8 under High Pressure. Issue 11 (February 2016) - Zhang, Huadi; Jin, Xilian; Lv, Yunzhou; Zhuang, Quan; Liu, Yunxian; Lv, Qianqian; Li, Da; Bao, Kuo; Liu, Bingbing; Cui, Tian
Abstract: First‐principles calculations and structure prediction simulations for the SnHn (n = 0.33—8) series using the ELocR code reveals the presence of a new SnH8 crystal with space group I$\bar 4$ m2 aside of the common SnH4 at 150—350 GPa.